Tourism product/ service attribute influence on overall tourist satisfaction level in Riga - Medne, Ilze; Berzina, Kristine; Van der Steina, Aija (University of Latvia, 2019)
Tourist satisfaction is significant for successful destination marketing as it affects the choice of destination, consumption of tourism products and services as well as the decision to return to the destination and intentions to recommend the destination to other potential tourists. The mutual positive influence of customer satisfaction and loyalty is indisputably proven by empirical research studies carried out in different economic fields and industries, including tourism. The aim of the research was to study the satisfaction level of foreign tourists as consumers with various tourism product attributes in Riga and its influence on overall satisfaction and further consumer behaviour of tourists. The method used in this research is the Penalty/Reward factor analysis method, which was developed by Brandt and afterwards used by many researchers to investigate the influence of different service attributes on the overall satisfaction level. The research is based on data of a tourist survey carried out in Riga in the summer of 2018. The data acquired in the survey allowed for conducting the Penalty/Reward analysis which represents an important instrument for establishing the trip elements or factors the absence or poor performance of which (low quality) causes customer dissatisfaction (decrease in the overall level of satisfaction) and the factors which cause increased customer satisfaction (rise in the overall level). Main results and findings are intended for a destination marketing organisation of Riga. The recommendations made by the authors will facilitate the improvement of the opportunities offered by Riga’s tourism industry in accordance with the foreign tourist requirements, thus raising the satisfaction level of foreign tourists.
Keywords: tourist satisfaction; product/ service attributes; penalty factors; reward factors; Research Subject Categories::SOCIAL SCIENCES::Business and economics